Complete mitochondrial genome of Empoasca vitis (Hemiptera: Cicadellidae). (3rd March 2016) - Zhou, Ningning; Wang, Mengxin; Cui, Lin; Chen, Xuexin; Han, Baoyu
Abstract: The complete mitochondrial genome of Empoasca vitis was sequenced. The length of the mitogenome is 15, 154 bp with 78.35% AT content (GenBank accession No. KJ815009). The genome encode 37 typical mitochondrial genes including 22 transfer RNA genes, 13 protein-coding genes, 2 ribosomal RNA genes and an A+T-rich region. The gene arrangement is similar to that of Drosophila yakuba, the presumed ancestral insect mitochondrial gene arrangement. Except for cox2 using GTG as start codon, other protein-coding genes (PCGs) share the start codons ATN. Usual termination codon TAA and incomplete stop codon T are using by 13 protein-coding genes. The A+T-rich region has a length of 977 bp with the AT content high to 88.95%.